Evaluation Of The Jombang Healthy Card Program Policy For The Poor In Jombang Regency - Annisah, Khoirotun; Muljanto, Muhammad Agus (UNIVERSITAS PAKUAN, 2024)
The Jombang Healthy Card program is a breakthrough issued by the Jombang Regency Government as a form of assistance for poor people who are not yet covered by national health insurance to obtain adequate health services. This research aims to determine the evaluation of the Jombang Healthy Card program policy for the poor at the Jombang Regency Social Service using the theory of William N. Dunn (2017) which has six evaluation criteria including effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. This research method is descriptive qualitative with data collection techniques through interviews, observation and documentation. The results of this research indicate that the evaluation of the Jombang Healthy Card program policy for the poor is still not optimal, with the following explanation: 1) effectiveness, still hampered by administrative problems, public perception and range of access to services resulting in objectives not being optimally achieved, although program monitoring is successful. 2) efficiency, human resources are efficient, but time and infrastructure are still not efficient. 3) adequacy, benefits felt by participants, but not enough to overcome the problem of health service costs for target groups who have not been recorded as participants. 4) equity, program socialization has been carried out, but participation is still not evenly distributed. 5) responsiveness, successful in getting positive responses from poor communities accompanied by constructive input on the Jombang Sehat Card program. 6) appropriateness, implementation is correct but needs to be improved so that the benefits can be felt by more target groups.